2010
DOI: 10.1159/000302721
|View full text |Cite
|
Sign up to set email alerts
|

Early and Sustained Systemic and Renal Hemodynamic Effects of Intravenous Radiocontrast

Abstract: Background and Aims: To measure the extended renal hemodynamic changes induced by intravenous radiocontrast. Methods: Cross-ewes were studied in a randomized cross-over study. Intravenous saline or radiocontrast were administered, and continuous measurement of cardiac output and renal blood flow (RBF) was performed with flow probes. Results: Radiocontrast induced early but transient increases in cardiac output with vasodilatation, followed by return to baseline values within 2 h. There was an initial decline i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…21 In support of this idea is the knowledge that during situations such as major surgery, renal artery occlusion of up to 80% for 2 hours does not cause long-term renal dysfunction. 22 Furthermore, septic AKI has been shown to manifest in situations of renal vasodilatation and normal or even increased renal blood flow. 20 Finally, unlike ischemic damage in which there is tubular cell necrosis, sepsis-induced AKI has a noticeable absence of tubular necrosis, and rather has only patchy, heterogeneous tubular cell injury with apical vacuolization, and can even be devoid of extensive apoptosis.…”
Section: Causes Of Aki: Ischemia Versus Sepsismentioning
confidence: 99%
“…21 In support of this idea is the knowledge that during situations such as major surgery, renal artery occlusion of up to 80% for 2 hours does not cause long-term renal dysfunction. 22 Furthermore, septic AKI has been shown to manifest in situations of renal vasodilatation and normal or even increased renal blood flow. 20 Finally, unlike ischemic damage in which there is tubular cell necrosis, sepsis-induced AKI has a noticeable absence of tubular necrosis, and rather has only patchy, heterogeneous tubular cell injury with apical vacuolization, and can even be devoid of extensive apoptosis.…”
Section: Causes Of Aki: Ischemia Versus Sepsismentioning
confidence: 99%
“…The relevance of such findings to a condition which leads to peak GFR losses at 72 h is open to question. We recently used a validated methodology to measure systemic and renal hemodynamics directly, accurately, and over several days by implanted transit-time flow probes [ 15 - 17 ] and found that, contrary to expectation, intravenous contrast administration induced only short-lived renal vasoconstriction (first hour) followed by sustained (days) renal vasodilatation and increased RBF [ 18 ]. However, such observations may not apply to the most common trigger of CIAKI: intra-arterial boluses of radiocontrast given over a short time during PCI.…”
Section: Introductionmentioning
confidence: 99%